Excess Repair Time for a Repairable System - AGRAFIOTIS, G. K. (Institutional Knowledge at Singapore Management University, 1990)
In this paper we deal with a repairable system and the topic of investigation is the total of all excess repair times--an excess repair being that repair the duration of which exceeds a given constant [tau]. The mean of this total excess repair time to the mean of the total repair time in (0, t), provides a useful measure of overtime repair. We also derive expressions for the distribution function of the time to the instant of the beginning of the first excess repair.